(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the problems associated with water resources, their current state and the level of pollution. It is highlighted that the global decline and deterioration of water resources are directly related to climate change, rapid population growth, improper use of water in industry and agriculture, and overexploitation of groundwater. It also examines the negative impact of water scarcity and pollution on human health, the economy, and ecological systems. Based on World Bank reports, the importance of water resource management in the transition to a green economy is revealed. The problems presented in the study are also relevant in the conditions of Uzbekistan, and the need for the protection and rational use of water resources is justified.